2013
DOI: 10.1089/aid.2013.0048
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Klotho Levels Were Inversely Associated with Subclinical Carotid Atherosclerosis in HIV-Infected Patients Receiving Combined Antiretroviral Therapy

Abstract: Combined antiretroviral therapy (cART) has significantly improved the survival rate in HIV-infected individuals, but it contributes to the development of various metabolic complications. Klotho is a novel antiaging gene that encodes a protein with pleiotropic functions, including an emerging role in cardiovascular disease (CVD). The protective effect of higher plasma klotho levels against CVD was recently observed in non-HIV-infected adults. We aimed to assess whether plasma-secreted α-klotho is associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Klotho, which is a kind of anti-aging protein [9], is involved in various pathologies, such as atherosclerosis, heart damage, hypertension, acute kidney injury, chronic kidney disease, diabetes mellitus, and even cancer [7, 8, 10, 11]. In a Klotho-deficient mouse aging-model study, Kuro-o et al reported that Klotho deficiency is closely related to cardiovascular diseases, such thatit enhances arteriosclerosis, extensive medial calcification of the aorta, and medial calcification and intimal thickening of medium-sized muscular arteries [9].…”
Section: Introductionmentioning
confidence: 99%
“…Klotho, which is a kind of anti-aging protein [9], is involved in various pathologies, such as atherosclerosis, heart damage, hypertension, acute kidney injury, chronic kidney disease, diabetes mellitus, and even cancer [7, 8, 10, 11]. In a Klotho-deficient mouse aging-model study, Kuro-o et al reported that Klotho deficiency is closely related to cardiovascular diseases, such thatit enhances arteriosclerosis, extensive medial calcification of the aorta, and medial calcification and intimal thickening of medium-sized muscular arteries [9].…”
Section: Introductionmentioning
confidence: 99%
“…Fourteen studies were conducted from Europe, 20,2226,30,31,34,35,39,41–43 followed by America (4 studies), 10,27,28,38 Asia (4 studies), 11,21,29,32 and Africa (4 studies). 33,36,37,40 There are four studies using CIMT ≥ 0.78 mm criteria, 32,36,37,40 eight studies with CIMT ≥ 0.80 mm, 10,22,27,28,30,31,34,35 10 studies with CIMT ≥ 0.90 mm, 11,21,2326,38,41,43 and four studies with CIMT ≥ 75th.…”
Section: Resultsmentioning
confidence: 99%
“…33,36,37,40 There are four studies using CIMT ≥ 0.78 mm criteria, 32,36,37,40 eight studies with CIMT ≥ 0.80 mm, 10,22,27,28,30,31,34,35 10 studies with CIMT ≥ 0.90 mm, 11,21,2326,38,41,43 and four studies with CIMT ≥ 75th. 20,29,33,39…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An inverse association to mortality has been reported, with higher circulating levels of sKl associated with increased survival in the general population as well as those with dialysis‐dependent kidney disease . sKl has also been linked to improved cardiovascular outcomes, inverse associations of sKl levels with both carotid artery intimal thickness and coronary artery disease in adults with normal renal function. Similarly in patients with CKD, sKl has shown inverse correlations to arterial stiffness, carotid artery intimal thickness and left ventricular dysfunction …”
Section: Markers and Assaysmentioning
confidence: 99%